Indoor UAV positioning using stereo vision sensor - Mohd Mustafah, Yasir; Azman, Amelia Wong; Akbar, Fajril (Elsevier, 2012)
The UAV system has becoming increasingly popular in the application such as surveillance, reconnaissance, mapping and many more. Different from guided vehicles, which rely on the pilot to navigate the system, UAV relies on autonomous control to provide this functionality. Hence, precise feedback on the position of the UAV is very important. Unlike outdoor positioning, there are no standard, low cost indoor positioning systems available. Hence, we proposed to utilize a stereo vision sensor as an indoor positioning system for our UAVs. The system utilizes two video cameras for stereo vision capture and set of fast algorithms so that position information can be obtained in real-time. Experiment conducted shows that the system could provide a reliable accuracy in real-time.